Do family firms matter in IPO markets? Initial returns performance of family and non-family firms – a critical perspective: Australian evidence. (21st July 2009) - Mroczkowski, Nicholas A.; Tanewski, George
This study examines the initial price performance of family and non-family controlled IPO firms listed on the Australian Securities Exchange (ASX) between 1988 and 1999. Ownership and control are significant factors that influence managerial incentives, whereas the dynamics underlying family relationships reduce agency costs, improve efficiency and positively impact on firm performance. The study finds evidence of lower (15.54%) initial underpricing on the first day of trading for family firms compared with non-family IPOs (36.12%) after adjusting for industry effects. The results also show a positive and significant association between firm value and fractional ownership for both family and non-family firms, which indicates that family and non-family IPO firms use fractional ownership to signal the value of the firm. These findings provide empirical support for signalling models articulated in the literature. Implications of these differences will allow market participants to make more informed investment choices. For example, investors seeking higher immediate returns might choose to invest in non-family firms rather than in family controlled firms.